PENGARUH DOSIS Trichoderma spp. DAN KOMPOSISI MEDIA TERHADAP PERTUMBUHAN BIBIT DURIAN (Durio zibethinus, L.) - Wibowo Wibowo; Agus Suprapto; Murti Astiningrum (Universitas Tidar, 2018)
The research studied the effect of dose Trichoderma spp. and composition media on growth durian seedling (Durio zibetinus, L.). Experiment conducted in August until Oktober 2016. Location of experiment in Perbotan, Kalisari, Tempuran, Magelang, Central Java. The latitude of 415 m above sea level, the soil type Latosol with a pH of 6,0. The research method used factorial experiment (3 x 4) are arranged in a complete randomized block design with three replications. The first factor was a goat manure of 1 : 0, 1 : 1, 1 : 2, and 1 : 3. The second factor was the Trichoderm spp. that was 0, 200 and 400 ml/plant. The result of the research a goat manure matter in 1 : 1 increased on lenght of shoots, fresh weight of shoots, dry weight of shoots, fresh weight of roots, and dry weight of roots. Most Trichoderma spp. 200 ml/plant increased on dry weight of shoots, fresh weight of roots, and dry weight of roots. Interaction a goat manure and Trichoderma spp. increased on dry weight of shoot, fresh weight of roots, and dry weight of roots.